Think & grow rich - Hill, Napoleon, 1883-1970.; Slattery, Joe. (Los Angeles, CA : Audio Renaissance ; New York : Distributed by St. Martin's Press, 1986)
Inspired by the lessons he learned while a protogé of Andrew Carnegie, Hill offers the money-making secrets that earned Carnegie and others unprecedented material and spiritual riches.
Unabridged.
In container (19 cm.).
Read by Joe Slattery.
Keywords: Carnegie, Andrew, -- 1835-1919.; Success in business